2015
DOI: 10.1080/10550887.2015.1127717
|View full text |Cite
|
Sign up to set email alerts
|

Substance use and misuse in burn patients: Testing the classical hypotheses of the interaction between post-traumatic symptomatology and substance use

Abstract: Background: We aimed to test whether the three classical hypotheses of the interaction between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Alcohol abuse was reported in 6.9% of patients in our study, a high rate compared to the average of 4.2% in the Spanish population in 2019 51 . These figures are consistent with those reported by Eiroa-Orosa, who showed that a higher proportion of burn patients had a history of substance abuse compared with the general population 52 .…”
Section: Discussionsupporting
confidence: 92%
“…Alcohol abuse was reported in 6.9% of patients in our study, a high rate compared to the average of 4.2% in the Spanish population in 2019 51 . These figures are consistent with those reported by Eiroa-Orosa, who showed that a higher proportion of burn patients had a history of substance abuse compared with the general population 52 .…”
Section: Discussionsupporting
confidence: 92%
“…This includes people in danger of social exclusion and already suffering serious mental health problems and illegal drug use. In both cases these groups made up almost one third of the sample, well above rates registered in other burn samples [55,12]. In these cases, the characteristics of the accident that caused the burn may be related to high risk activities such as copper theft from street lights or the drowsiness caused by the consumption of benzodiazepines.…”
Section: Discussionmentioning
confidence: 90%
“…While the time until the patient was found unconscious in sauna was not known, the period recorded in other studies was 30 minutes to 1 hour [3]. In comparison with the general population, higher rates of substance abuse, misuse were seen in the patients with burn injury [8,9,10,11]. Substance abuse in burn injury patients was reported to be an aggravating condition in patients` recovery.…”
Section: Discussionmentioning
confidence: 94%